Analyzing the role of emotional intelligence on work engagement among teachers. An application of the Job Demands-Resources theory - Mérida-López, Sergio (My University, 2021)
Empirical evidence has demonstrated that teaching professionals suffer from psychosocial risk factors associated with negative educational, economic, and social consequences (Iriarte-Redín & Erro-Garcés, 2020; Travers, 2017). According to the Job Demands-Resources theory, it is proposed that both contextual and personal factors are predictors of teachers’ job strain, work engagement, and numerous individual and organizational outcomes (Bakker & Demerouti, 2017; Granziera et al., 2021). Work engagement is highlighted as a key dimension in the teaching context given its positive effects on health, commitment, and performance at work. Recent studies have increasingly focused on the predictive role of teachers’ personal resources (e.g., self-efficacy, optimism, and emotional intelligence) in work engagement as well as in positive functioning outcomes (Granziera et al., 2021). Emotional intelligence (EI) has been underscored as a helpful personal resource among teachers relating to increased work-related health and well-being (Iriarte-Redín & Erro-Garcés, 2020; Mérida-López & Extremera, 2017). However, the role of EI on teachers’ work engagement has not been empirically tested based upon the Job Demands-Resources theory. Better knowledge about the relationship between EI and contextual and personal factors in explaining teachers’ work engagement and work-related and personal well-being indicators would substantially contribute to the development of effective Positive Organizational Psychology intervention programs in educational settings. Therefore, the main goal of the current dissertation was to integrate existing theoretical frameworks on emotional intelligence and work-related well-being in providing novel empirical research offering a more comprehensive view regarding the effects of EI on teachers’ work engagement.
Análisis del papel de la inteligencia emocional en el engagement laboral del profesorado. Aplicación de la teoría de Demandas y Recursos Laborales
Keywords: Profesores; Mercado de trabajo; Tesis doctorales; Emociones; Emotional intelligence; Work engagement; Teachers; Job Demands-Resources theory; Dissertation